2022
DOI: 10.1128/mbio.01183-22
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Bacterial Community Potentiates Clostridioides difficile Infection Severity

Abstract: Clostridioides difficile colonization can be asymptomatic or develop into an infection ranging in severity from mild diarrhea to toxic megacolon, sepsis, and death. Models that predict severity and guide treatment decisions are based on clinical factors and C. difficile characteristics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 89 publications
2
29
0
Order By: Relevance
“…27 And the elevated abundance of Enterococcus , Helicobacter , and Klebsiella in the gut was often accompanied by severe CDI. 70 Engevik et al observed co-colonization of C. difficile and Fusobacterium nucleatum in feces and tissue sections of CDI patients, and F. nucleatum was able to significantly increase C. difficile biofilm and extracellular polysaccharide production. 81 Probiotics that are antagonistic to C. difficile and its mutualistic microbes can effectively curb their ecological dominance, e.g.…”
Section: Advantages and Disadvantages Of “Bacteria–drug Combination”mentioning
confidence: 99%
See 1 more Smart Citation
“…27 And the elevated abundance of Enterococcus , Helicobacter , and Klebsiella in the gut was often accompanied by severe CDI. 70 Engevik et al observed co-colonization of C. difficile and Fusobacterium nucleatum in feces and tissue sections of CDI patients, and F. nucleatum was able to significantly increase C. difficile biofilm and extracellular polysaccharide production. 81 Probiotics that are antagonistic to C. difficile and its mutualistic microbes can effectively curb their ecological dominance, e.g.…”
Section: Advantages and Disadvantages Of “Bacteria–drug Combination”mentioning
confidence: 99%
“…69 Whether it is a traditional probiotic or a new live biologic, mainstream clinical use has chosen to use probiotics after antibiotics, and there may be multiple reasons for such a combination order (Fig. 1): (1) the subsequent addition of probiotics can effectively occupy these ecological sites, thus competing to exclude the more resistant C. difficile strains, vegetative cells and spores; 9 (2) the addition of probiotics competes with the remaining C. difficile strains and their vegetative cells for nutrients essential for growth such as carbohydrates and amino acids, thus inhibiting the normal growth and metabolism of C. difficile; 19 (3) probiotics are able to secrete organic acids after colonization and affect the level of intestinal bile acid metabolism, especially enhancing the level of secondary bile acids, thus altering the intestinal growth environment to the detriment of C. difficile; 49,50 (4) after colonization, probiotics can secrete antimicrobial peptides, bacteriocins, extracellular polysaccharides and other types of antimicrobial substances, which have a direct killing effect on C. difficile strains; 64,[70][71][72] (5) probiotics can activate the intestinal immune system and enhance the related immune response to clear C. difficile; 73 and (6) probiotics can indirectly promote the growth of low-abundance beneficial microbes in the gut by "cross-feeding", thus co-antagonizing C. difficile. 74 Fig.…”
Section: Mode Of Action Of Probiotics In the Gutmentioning
confidence: 99%
“…From the remaining sixteen studies, two were excluded for not reporting dat Clostridioides difficile and Enterococcus spp. 's interaction in the gut microbiota [10 Therefore, 14 studies were included in this systematic review (Figure 1) [1,[12][13][14][15][16][17][18][19][20][21][22][23][24]. O 14 included studies, 3 studies evaluated Enterococcus spp.…”
Section: Study Descriptionmentioning
confidence: 99%
“…'s interaction in the gut microbiota [10,11]. Therefore, 14 studies were included in this systematic review (Figure 1) [1,[12][13][14][15][16][17][18][19][20][21][22][23][24]. Of the 14 included studies, 3 studies evaluated Enterococcus spp.…”
Section: Study Descriptionmentioning
confidence: 99%
“…For example, bacteria capable of fiber degradation and bile acid metabolism were linked to less severe diseases. Meanwhile, some bacterial groups, including Escherichia , Streptococcus , Enterococcus , Helicobacter , and Klebsiella , were associated with worse infection outcomes ( Schubert et al, 2015 ; Lesniak et al, 2022 ). Much is known about the colonization resistance conferred by the gut microbiota; however, only recent studies have started to reveal the interactions between specific gut bacterial species and C. difficile .…”
Section: Introductionmentioning
confidence: 99%